Is ICT gendered? an understanding from the Orang Asli - Nwanesi Peter Karubi,; Goy, Siew Ching (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Why are we so resolute that men and women are different? This is because society divides people into feminine women and masculine men. Similarly, technology and new ideas impact differently on both men and women. In fact, studies on gender explore ways of seeing women and men as not just biological organisms, but as people formed by their everyday social world. Therefore, this paper examines the challenge of understanding gender issues, relations and patterns in the development of a Telecentre among the Orang Asli. This study of gender issues with regard to access to and utilization of ICTs was explored through community engagement. As against the back drop that the Orang Asli did not easily or readily accept new ideas or changes within their environment and lifestyles, this study discovered that the Orang Asli, as a whole, welcomed new ideas and technologies that would move them forward. But more importantly, they were not very particular, gender-wise, about who actually speared the drive to improve their wellbeing and change their fortune.